Do minimum wages improve self-rated health? Evidence from a natural experiment - Lucas Hafner; Benjamin Lochner (Empirical Economics, 2021)
We analyze whether the introduction of the general minimum wage in Germany in 2015 had an effect on workers' self-rated health. To this end, we use survey data linked to administrative employment records and apply difference-in-differences regressions combined with propensity score matching. This approach enables us to control for a vast set of potential confounding variables. We find a health improving effect among the individuals who were most likely to be affected by the reform. Our results indicate that workers' improved satisfaction with pay, their reduced working hours, and a reduction in time pressure at work may drive this result.
Keywords: I10; I18; J38; 330; Minimum wage; Self-rated health; Natural experiment